Triptolide Induces Apoptosis Through Fas Death and Mitochondrial Pathways in HepaRG Cell Line - You, Longtai; Dong, Xiaoxv; Ni, Boran; Fu, Jing; Yang, Chunjing; Yin, Xingbin; Leng, Xin; Ni, Jian (Frontiers in Pharmacology, 2018)
Triptolide isolated from the traditional Chinese herb Tripterygium wilfordii Hook F., possesses anti-tumor, anti-fertility and anti-inflammatory properties. Triptolide-induced hepatotoxicity has continued to engage the attention of researchers. However, not much is yet known about the cytotoxicity of triptolide, and the precise mechanisms involved. In the present study, we investigated the cytotoxicity of triptolide and its underlying mechanisms, using an in vitro model (HepaRG cell). The results demonstrated that triptolide significantly reduced cell viability and induced apoptosis in HepaRG cells in a dose- and time-dependent manner. Triptolide treatment also provoked reactive oxygen species (ROS) generation and depolarization of mitochondrial membrane potential (MMP). Moreover, triptolide dose-dependently increased the protein expression levels of Fas, Bax, p53, p21, cyclin E, cleaved caspase-3, 8 and 9; and subsequent cleavage of poly (ADP-ribose) polymerase (PARP). However, the protein expression of Bcl-2, cyclin A and CDK 2 were significantly decreased. These results suggest that triptolide inhibits cell proliferation and induces apoptosis via the Fas death pathway and the mitochondrial pathway.